Toxic organo-chlorine compounds in the chlorinated drinking water of the Dnipro basin cities (Environment & Health, 2016)
Objective. We identified and evaluated the factual THM and HAA levels in drinking water under the chlorination (chloramine, chlorine gas) at different stages of water treatment in waterм. We investigated the water of the rivers’ Dnipro and Desna water-supply purified and disinfected with the application of the chlorination with preammoniation. At the metallurgical work’s water-pipe in Zaporizhzhia, water was studied after the purification at the treatment facilities similar to the Kyiv ones, but chlorine gas was used instead of chloramine in water treatment there. 7 volatile and 9 non-volatile OCCs (THM and HAA) were identified in drinking water. The determination was carried out using the standardized methods with the help of the gas chromatograph "Kristalliuks 4000-M ".Results. Investigations, performed at the Kyiv water pipes, demonstrated a presence of organo-chlorine compounds in drinking water: volatile THMs (chloroform and dichlorobromomethane) and non-volatile OCCs (monochloroacetic and trichloroacetic acids) within the limits of the MAC. Not only the high levels of chloroform (>2 MPC) but also much higher concentrations of monochloroacetic and trichloroacetic acids than at the Kyiv water-supplies were identified in drinking water at the metallurgical work’s water-pipe in Zaporizhzhia.Conclusions. We established that volatile (THM) and non-volatile (HCS) toxic OCCs were formed under the Dnipro basin water chlorination simultaneously. Chloroform is a prior among the THMs formed in water and monochloroacetic acid (MCAA) - for HAA. The content of HF and MCAA in water of treatment facilities does not exceed the established standards where the chlorination with preammoniation is used. At the concentrations above the allowable levels, application of chlorine gas in water treatment leads to the formation of chloroform and MCAA (in some water samples).
Keywords: drinking water; water treatment; chlorination (chloramine; chlorine gas); organo-chlorine compounds; volatile THM; non-volatile HAA